1997
DOI: 10.1046/j.1469-8137.1997.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and substrate specificity of an extracellular fructanhydrolase from Lactobacillus paracasei ssp. paracasei P 4134

Abstract: SUMMARYA novel extracellular fructanhydrolase was isolated from the culture filtrate of Lactobacillus paracasei ssp. paracasei P4134 grown on a mineral medium supplemented with fructan extracted from Timothy {Phleum pratense L.) as the only carbon source. The enzyme was purified by a combination of ammonium sulphate precipitation, affinity chromatography, preparative isoelectric focusing and anion-exchange chromatography. As a result of these procedures, the specific enzyme activity increased 93-fold, with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…paracasei previously grown on FOS (Goh et al, 2007). In agreement with a previous biochemical characterization of a fructanhydrolase of L. paracasei (Müller and Seyfarth, 1997), the analysis of the degradation products of L. paracasei 1195 FosE indicated that it is an exofructanhydrolase (Goh et al, 2007). The transcriptional regulation of the fos cluster has also been studied.…”
Section: Figure 2 Fructan Utilization Pathways Characterized In Labsupporting
confidence: 81%
See 2 more Smart Citations
“…paracasei previously grown on FOS (Goh et al, 2007). In agreement with a previous biochemical characterization of a fructanhydrolase of L. paracasei (Müller and Seyfarth, 1997), the analysis of the degradation products of L. paracasei 1195 FosE indicated that it is an exofructanhydrolase (Goh et al, 2007). The transcriptional regulation of the fos cluster has also been studied.…”
Section: Figure 2 Fructan Utilization Pathways Characterized In Labsupporting
confidence: 81%
“…paracasei P 4134 provided the first clues on the fructan degradative pathways of lactobacilli (Müller and Seyfarth, 1997). The enzyme hydrolized β-2,6 linked fructans more rapidly than β-2,1 linked fructans and the main product of hydrolysis was fructose, suggesting that the enzyme is an exofructanase (Müller and Seyfarth, 1997). Later studies on other L. casei/paracasei have confirmed these conclusions (Kuzuwa et al, 2012;Velikova et al, 2017).…”
Section: Metabolic Pathways For Fructans Utilizationmentioning
confidence: 92%
See 1 more Smart Citation